Peripheral Nerve Diffusion Tensor Imaging: Assessment of Axon and Myelin Sheath Integrity - Heckel, A. (PLoS One, 2015)
PURPOSE: To investigate the potential of diffusion tensor imaging (DTI) parameters as in-vivo biomarkers of axon and myelin sheath integrity of the median nerve in the carpal tunnel as validated by correlation with electrophysiology. METHODS: MRI examinations at 3T including DTI were conducted on wrists in 30 healthy subjects. After manual segmentation of the median nerve quantitative analysis of fractional anisotropy (FA) as well as axial, radial and mean diffusivity (AD, RD, and MD) was carried out. Pairwise Pearson correlations with electrophysiological parameters comprising sensory nerve action potential (SNAP) and compound muscle action potential (CMAP) as markers of axon integrity, and distal motor latency (dml) and sensory nerve conduction velocity (sNCV) as markers of myelin sheath integrity were computed. The significance criterion was set at P=0.05, Bonferroni corrected for multiple comparisons. RESULTS: DTI parameters showed a distinct proximal-to-distal profile with FA, MD, and RD extrema coinciding in the center of the carpal tunnel. AD correlated with CMAP (r=0.50, p=0.04, Bonf. corr.) but not with markers of myelin sheath integrity. RD correlated with sNCV (r=-0.53, p=0.02, Bonf. corr.) but not with markers of axon integrity. FA correlated with dml (r=-0.63, p=0.002, Bonf. corr.) and sNCV (r=0.68, p=0.001, Bonf. corr.) but not with markers of axon integrity. CONCLUSION: AD reflects axon integrity, while RD (and FA) reflect myelin sheath integrity as validated by correlation with electrophysiology. DTI parameters consistently indicate a slight decrease of structural integrity in the carpal tunnel as a physiological site of median nerve entrapment. DTI is particularly sensitive, since these findings are observed in healthy participants. Our results encourage future studies to evaluate the potential of DTI in differentiating axon from myelin sheath injury in patients with manifest peripheral neuropathies.